Stereoselective synthesis of β-carboethoxy-γ-lactams via imino Mukaiyama aldol-type reaction of 1,4-bis(trimethylsilyloxy)-1,4-diethoxy-1,3-butadiene - Manat Pohmakotr (2018)
The reaction of the (bis)trimethylsilyloxy derivative of diethyl succinate with imines in the presence of ZnCl2provides a general stereoselective entry to β-carboethoxy-γ-lactams. © 2007 Elsevier Ltd. All rights reserved.